'A Strikers' "Soviet" in Belfast'? The Great Belfast Strike of 1919. Issue 3 (1st December 2022) - Coquelin, Olivier
Abstract : The Great Belfast Strike of January–February 1919, although hardly explored until now, was part of the movement to reduce the working week, which affected large British industrial centres in the aftermath of the First World War. Apart from its longevity (four weeks), this social dispute was characterized by its organizational mode, which some, notably in the English and Irish press, went as far as to equate with that of a local soviet. Since revolutionary Ireland was to be the scene of a hundred or so experiments in workers' self-management under the name of 'soviet', mainly in the south and south-west of the island, it is therefore questionable whether the Belfast Strike Committee encompassed 'some of the attributes of an industrial Soviet', as the Manchester Guardian 's correspondent argued, and if so, to what extent it paved the way for the subsequent Irish soviets. To this end, this article sets out to conduct a comparative study using the 'Irish Soviets' methods' – as defined by one of the protagonists of the Drogheda soviet of September 1921 – as an analytical tool.